Legal provisions of the Oil Products Distribution Company - محمد, محمد جاسم (Journal of Petroleum Research and Studies, 2021)
The international oil companies have a good budget of increasing profitability as a result of the positive change in the world oil prices, which has reflected positively on the profitability and productivity of international oil companies, and the most prominent domestic companies that were positively affected by global variables is the oil products distribution company products as a one of the public companies that are administratively associated with the Ministry of Oil. In legal terms, however, it is subject to several laws, most notably the Law for the Establishment of Oil Products Distribution Company No. (1) of 1999, the Law of Organization of the Ministry of Oil No. 101 of 1976, Public companies No. (22) for the year 1997 can be determined these laws and legal provisions concerning the establishment, management and how the distribution of profits and losses in which the mechanism of oversight procedures, the end of the cases it expires, filtered, and we will discuss in this paper the most important legal provisions relating to the distribution of petroleum products company.